Pemberdayaan Kelompok Peternak Melalui Sosialisasi Pembuatan Jerami Padi Fermentasi sebagai Pakan Ternak Sapi di Desa Bakti Agung Kabupaten Poso - Uti Nopriani; Marten Pangli; Suwardhi Pantih (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service activity aims to deliver knowledge to farmer group so that they can improve their skills in making fermented rice straws for animal feed. The study methods used were survey, lecture, discussion, question and answer, socialization and evaluation. The target of the service activity is the farmer group. The socialization carried out explained the materials and tools used for fermenting rice straw, the nutrition quality of rice straw, the benefits of fermented rice straw, and the processing techniques of fermented rice straw. The results of the activity evaluation showed that farmer group knowledge concerning the materials and tools used for fermenting rice straw increased by 46,25%, knowledge regarding the nutrition quality of rice straw increased by 40,98%, knowledge about the benefits of fermented rice straw increased by 42,67% and knowledge of fermented rice straw processing techniques increased by 40,28%.